Acidity amelioration and nutrient management practices for mitigating yield constraints of rice in Vaikom Kari - Devi V S (Department of Agronomy, College of Agriculture, 2017)
An investigation entitled “Acidity amelioration and nutrient management practices for mitigating yield constraints of rice in Vaikom Kari” was carried out as two field experiments in Vaikom Kari soils of Kuttanad during the period from 2014 to 2017 to standardize acidity amelioration and nutrient management practices for rice to overcome yield constraints in Vaikom Kari and to work out the economics of cultivation. Experiment I entitled “Evaluation of acidity amelioration practices for rice in Vaikom Kari” was conducted in farmer’s field in Kallara panchayat in Kottayam district during November 2014 to March 2015. The experiment was laid out in RBD with seven treatments in three replications with rice var. Uma. The treatments included lime, dolomite and rice husk ash (RHA) applied as two splits- as basal + 30 DAS or as basal + one week before third dose of fertilizer application and a control without ameliorants. Lime, dolomite or RHA, irrespective of time of application, could produce taller plants with higher LAI and tiller number at maximum tillering (MT), panicle initiation (PI) and harvest stages. The same treatments recorded higher number of panicles m-2 and 1000 grain weight and lower sterility percentage. Lime, dolomite or RHA as basal + 30 DAS produced significantly higher grain yield over control. Grain yield was significantly and positively correlated with LAI at MT and PI stages and panicle number m-2. Higher straw yield was obtained with lime or dolomite as basal + 30 DAS and RHA treatments. Application of lime, dolomite or RHA as basal + 30 DAS resulted in higher dry matter production at harvest. Soil ameliorants improved the uptake of macronutrients and micronutrients. Uptake of N and K were significantly higher for lime, dolomite or RHA applied as basal + 30 DAS while dolomite as basal + 30 DAS recorded the highest P uptake. The highest uptake of Ca was found with lime as basal + 30 DAS and that of Mg and S with dolomite as basal + 30 DAS. The highest uptake of Mn and Zn were observed